Polymeric Membrane Sensors for Detection of Titanium (III) Ions Based on Tripodal-or Calixarene-Ligand and Detection of Ohromium (VI) Using Metallo-Salen Ionophores - Rezayi, Majid (2011)
Currently, despite of many developments in the field of ion selective electrodes (ISEs), it continues to evolve. The introduction of low detection limit ISEs may open a new opportunity to determine trace target ions. Improvements of detection limits, selectivities, understanding the response mechanism and developing new membrane materials are constantly being reported in the literatures. Moreover, the development of ISEs used in hospital and industrial setting as well as in clinical, environmental and physiological research has been opened new horizons in front of us. This research is focused on the fabrication of new PVC-membrane sensors based on tris(2pyridyl) methylamine, tpm and c-methylcalix[4]resorcinarene, CMCR as an cationic ionophores for detection of titanium (III) cation, and also N,N′Bis(salicylidene) ethylenediamino cobalt(II),Co(SALEN) as an anionic ionophore for determining the chromate (II) anion. The complex reactions of Co(SALEN) with chromate (II) anion, tpm and CMCR with titanium (III) cation in water (H2O), acetonitrile (AN) and their binary mixture solutions at different temperatures by using the conductometric method, are investigated. The characterization and evalution of materials are described. In addition, a variety of analytical methods, including UV-Vis spectroscopy, FT-IR spectroscopy, Scanning Electron Microscopy (SEM), are used to study these processes. Later on, the application and validation of proposed ISEs with the potentiometric titration, atomic absorption spectrometry (AAs) and inductively coupled plasma atomic emission spectrometry (ICP-AES) are studied. Based on conductometric measurement results, the stoichiometry of complex formation for all the cases of ion-ionophore is 1:1. Furthermore, the average of stability constant (logKf) obtained for tpm-Ti(OH)(OH2)52+, CMCRTi(OH)(OH2)52+ and Co(SALEN)-CrO42- complexes at 25⁰C are 2.70, 3.13 and 3.02, respectively. Therefore, the mentioned ionophores can be used as sensing elements to fabricate ISE membranes for determination of titanium and chromate ions. These electroactive composite materials resulted in three new ionophore types which one based on selective ion–sensing membrane electrodes. They were fabricated for the determination of Ti (III) and CrO4 ions in solutions. The membrane sensors showed fast, stable and Nernstian response for the cation of titanium (III) and anion of chromate (II) over the concentration range from 1.0×10-6 to 1.0×10-2 M and 1.0×10-6 to 1.0×10-1 M at 25⁰C, over the pH range from 1 to 2.5 and 7 to 10 respectively. For titanium (III)cation, based on tpm and CMCR ionophores, the Nernstian slopes, detection limits and response times were 29.17±0.24 and 30.38±0.15 mV/decade of activity , 7.9×10-7 and 8.9×10-7 M, 20 and 15 s, respectively. For chromate (II)anion, using Co(SALEN) ionophore, the Nernstian slope, detection limit and response time was -28.33±0.10 mV/decade of activity, 7.9×10-7 M and <10 s. The direct determination of 4 to 39 μg/ml of titanium (III) standard solution and 2 to 48.5 μg/ml of chromate (II) standard solution showed an average recovery of 94.60, 94.70 and 96.03 % and a mean relative standard deviation of 1.8, 2.2 and 1.6% at 100.0 μg/ml for tpm, CMCR and Co(SALEN) sensors, respectively. Finally, the utilizing of electrodes as the end point indicators for potentiometric titration with EDTA and Pb(NO3)2 solutions for titanium (III) and chromate (II) sensors were successfully carried out respectively.